Case Report: Disseminated actinomycosis-induced splenic rupture with spleen and liver abscesses - Li, Huaijuan; Cheng, Zhaoping; Li, Kui (Frontiers in Medicine, 2025)
Disseminated actinomycosis is a rare, slowly progressing infection caused by Actinomyces species and can manifest as the formation of multiple abscesses and sulfur granules in infected tissues. In this report of this rare disease, the pathogens were not traced at the initial stage, and extremely rare but dangerous complications occurred, resulting in a new research perspective for the early identification of this rare disease. This study reports a case of disseminated actinomycosis in a 59-year-old Asian female with a history of lung infection. She experienced splenic rupture after mild percussion performed due to abdominal pain, accompanied by fever and sepsis; the rupture was effectively managed with conservative treatment; however, she experienced delayed splenic rupture later. Pathological examination of spleen and liver biopsy samples revealed chronic suppurative inflammation with abscesses, and the surrounding hyphae were arranged radially, the metagenome next-generation sequencing of pus shows that it belongs to Actinomyces israelii. The patient was cured with splenectomy and comprehensive treatment, including anti-infective therapy combined with imipenem/cilastatin, penicillin and antishock therapy. The results of this study emphasize the importance of etiology tracing and accurate, early treatment for the disease. Moreover, if minor trauma leads to unexpected damage to internal organs, the possibility of the coexistence of other etiologies should be considered.